Influence and Mechanism Analysis of Green Digital Transformation on Enterprise Green Innovation - Meng, Qiantong; Meng, Qiantong (Transactions on Economics, Business and Management Research, 2024)
The purpose of this study is to explore the influence of green digital transformation (GDT) on enterprise green innovation (GI) and its mechanism. Under the background of increasingly severe global environmental problems and accelerating digital transformation, green innovation has become an important driving force for the sustainable development of enterprises. Therefore, this study has important theoretical and practical significance. In order to achieve the research purpose, this study adopts multiple linear regression model for empirical analysis. The research sample covers enterprises of different industries and sizes to ensure the universality and representativeness of the research. In the choice of variables, we not only pay attention to the relationship between GDT and GI, but also consider the possible influencing factors such as enterprise scale, enterprise age and industry attributes. Through empirical analysis, it is found that GDT has a significant positive impact on GI, which shows that GDT can effectively enhance the green innovation ability of enterprises. At the same time, the scale of enterprises has also been proved to have a positive impact on green innovation, while the influence of enterprise age and industry attributes is not significant. These findings provide a useful reference for enterprises to formulate green innovation strategies. Based on the research results, this paper puts forward some suggestions to enterprises and governments to promote GDT and green innovation. For enterprises, they should actively invest in green digital technology, cultivate green innovation consciousness and develop together with green supply chain partners. The government should provide support in policy, supervision and cooperation with Industry-University-Research to create a good environment for green innovation.